Role of Forkhead Box O Proteins in Hepatocellular Carcinoma Biology and Progression (Review) - Yang, Shaojie; Pang, Liwei; Dai, Wanlin; Wu, Shuodong; Ren, Tengqi; Duan, Yunlong; Zheng, Yuting; Bi, Shiyuan; Zhang, Xiaolin; Kong, Jing (Frontiers in Oncology, 2021)
Abstract. Hepatocellular carcinoma (HCC) is the most common type of malignant tumor of the digestive system and is associated with high morbidity and mortality. The main treatment for HCC is surgical resection. However, advanced disease, recurrence and metastasis are the main factors affecting prognosis. Chemotherapy and radiotherapy are not sufficiently efficacious for the treatment of primary and metastatic HCC; therefore, the optimization of targeted therapy is essential for improving outcomes. Forkhead box O (FOXO) proteins are widely expressed in cells and function to integrate a variety of growth factors, oxidative stress signals and other signals, thereby inducing the specific expression of downstream signal factors and regulating the cell cycle, cell senescence, apoptosis, oxidative stress, development and chemotherapy sensitivity. Accordingly, FOXO proteins are considered multifunctional cancer treatment targets. The present review discusses the roles of FOXO proteins, particularly FOXO1, FOXO3, FOXO4 and FOXO6, in HCC and establishes a theoretical basis for the potential targeted therapy of HCC.